Influencing factors of community empowerment for domestic waste prevention and management among people living in river basin: A scoping review - Neti Juniarti; Maulida Nurapipah; Desy Indra Yani; Citra Windani Mambang Sari (Wolters Kluwer Medknow Publications, 2021)
Citarum River in West Java, Indonesia, is the most polluted river in the world which pollutes the ocean. This is caused by lack of community empowerment for domestic waste prevention and management. This study aimed to identify factors influencing community empowerment for domestic waste prevention and management, as well as the intervention for improvement. A scoping review was conducted using databases such as Google Scholar, EBSCOhost, and PubMed with keywords such as community empowerment, domestic waste management, waste prevention, and healthy living, published from 2009 to 2019. Initially, a total of 57,339 articles were retrieved, and with inclusion and exclusion criteria, eight articles were included for this review. Based on the results, three influencing factors were found at the individual, community, and government level. Regarding the intervention, promoting people and participatory engagement were the most effective ways to empower people in promoting healthy and clean behavior. Further research is needed to improve community empowerment for waste management among people living in the river basin to reduce pollution from domestic waste.